Semiotika Kiblat: Analisis Peircean terhadap Tafsir At-Tanwir Muhammadiyah - Gaes Rizka Nugraha Nugraha; Haringun Trisiwi Adhi Rachmawati Trisiwi Adhi (Universitas Islam Negeri Sunan Kalijaga, 2025)
The significance of this study lies in the understanding that the concept of the qibla in Islam is not merely a geographical direction but a symbol of identity, unity, and spiritual orientation for Muslims. In the modern era, the interpretation of the qibla faces challenges due to the developments in science, culture, and societal dynamics. The material object of this research is the concept of the qibla as interpreted in Tafsir At-Tanwir, while the formal object is the semiotic analysis of Charles Sanders Peirce, which views signs as a triadic relationship between the representamen, object, and interpretant. This study aims to uncover the profound meanings of the qibla concept through a comprehensive semiotic approach. The research employs a qualitative descriptive-analytical method with Peirce's semiotic theory as the analytical framework. Primary data are derived from Tafsir At-Tanwir, authored by the Muhammadiyah Council for Tarjih and Tajdid, while secondary data include literature on semiotics, Quranic exegesis, and socio-cultural studies related to the concept of the qibla. The analytical technique involves identifying the three core elements of a sign—representamen, object, and interpretant—and exploring their interrelations within historical, social, and theological contexts. The findings reveal that the qibla concept in Tafsir At-Tanwir is interpreted in multiple dimensions: as the direction of worship, the exclusive identity of Muslims, a symbol of an egalitarian social system, and an instrument for shaping the ideal personality of an Islamic society.